PENGARUH KEMAMPUAN KERJA, BUDAYA KERJA, DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN PADA BANK BPR KANTI CABANG BATUBULAN GIANYAR - Nyoman Suryani; I Nyoman Mustika; I Nyoman Susila Nanda Pramuja (VALUES, 2023)
Human resources are something that is very influential for the progress of an institution. Without quality human resources an institution will not develop. This study aims to determine and analyze the influence of work ability, work culture, and work motivation on employee performance at Bank Bpr Kanti Batubulan, Gianyar. This research was conducted at Bank Bpr Kanti Batubulan, Gianyar. The objects in this study are work ability, work culture, and work motivation. The population and sample used in this study were 40 employees at Bank Bpr Kanti Batubulan, Gianyar. Sampling using the census method because the population is less than 100. Data collection is done through interviews and questionnaires. The data analysis technique used wasmultiple linear regression analysis which was processed using SPSS version 25 software. The results showed that work ability, work culture, and work motivation had a positive and significant effect on employee performance at Bank Bpr Kanti Batubulan Gianyar. It can be interpreted that if the employee's work motivation increases, it will be followed by an increase in employee performance at Bank Bpr Kanti Batubulan Gianyar.